Absence of evidence for post-training tDCS effects on motor memory consolidation and premotor–primary motor cortex interaction: a resting-state EEG study - Dabbagh, Alhuda; Idaji, Mina Jamshidi; Tzvi, Elinor; Nikulin, Vadim; Rumpf, Jost-Julian; Classen, Joseph (Frontiers in Human Neuroscience, 2026)
IntroductionMotor memory consolidation may be influenced by offline application of non-invasive brain stimulation to the primary motor cortex (M1). One potential underlying mechanism involves changes in oscillatory neuronal activity within the premotor and primary motor cortices, as well as their interaction.MethodsTwenty-four healthy young participants (age 22.9 ± 2.9 years, mean ± SD) participated in two experimental sessions: a post-training sham and real transcranial direct current stimulation (tDCS) intervention. The anode was placed over the left M1, and stimulation was applied immediately after training of an explicit sequential finger tapping task. The task was repeated 8 h later to assess between-session performance changes, serving as an indicator of the effectiveness of the post-training offline motor memory consolidation process. High-density resting-state electroencephalography was recorded before training and after tDCS to examine beta frequency power, functional connectivity, and directed information flow between M1 and the dorsal premotor cortex (dPMC).Results and discussionWe observed no meaningful post-training tDCS effects on motor consolidation relative to the sham intervention. Likewise, we found no evidence that post-training tDCS altered beta-band functional connectivity or directed information flow between the left M1 and dPMC. Our findings, therefore, do not provide evidence for a meaningful effect of post-training tDCS of M1 on the offline motor memory consolidation process. However, independent of intervention type, significant post-training increases in beta-frequency power were observed across M1 and dPMC subregions. An exploratory follow-up analysis indicated that stronger directional interactions from M1 to the dPMC could be related to enhanced motor consolidation—a hypothesis that should be further investigated in future studies.